Blind Channel Equalization Using Constrained Generalized Pattern Search Optimization and Reinitialization Strategy. (22nd December 2008) - Zaouche Zaouche, Abdelouahib Abdelouahib; Dayoub Dayoub, Iyad Iyad; Rouvaen Rouvaen, Jean Michel Jean Michel; Tatkeu Tatkeu, Charles Charles
Abstract : We propose a global convergence baud-spaced blind equalization method in this paper. This method is based on the application of both generalized pattern optimization and channel surfing reinitialization. The potentially used unimodal cost function relies on higher- order statistics, and its optimization is achieved using a pattern search algorithm. Since the convergence to the global minimum is not unconditionally warranted, we make use of channel surfing reinitialization (CSR) strategy to find the right global minimum. The proposed algorithm is analyzed, and simulation results using a severe frequency selective propagation channel are given. Detailed comparisons with constant modulus algorithm (CMA) are highlighted. The proposed algorithm performances are evaluated in terms of intersymbol interference, normalized received signal constellations, and root mean square error vector magnitude. In case of nonconstant modulus input signals, our algorithm outperforms significantly CMA algorithm with full channel surfing reinitialization strategy. However, comparable performances are obtained for constant modulus signals.